Profil Psikologis Atlet Pekan Olahraga Nasional (PON) Papua Menuju PON XX Tahun 2020 - Muhammad Fadli Dongoran; Chyntia Novita Kalalo; Syamsudin (UIR Press, 2020)
This study aimed to identify the psychological profile of athletes PON Papua. In addition, each psychological aspect of Athlete PON Papua will be analyzed the condition of each psychological aspect along with the spread of athletes and their presentation. The method used in this study is a survey method with expost facto research design. The population in this study are athletes Papua who will be prepared road to PON XX 2020. The sampling technique used purposive sampling with the criteria for athletes PON Papua who had conducted training camps Papua Province in 2019. Based on that, the research samples obtained from athletes in sports are; Handball, Softball, Athletics, Cricket, Futsal, Basketball, Pencaksilat totaling 101 athletes. Data collection uses the Psychological Skills Inventory for Sports (PSIS) questionnaire. The results showed that the psychological profile of athletes PON Papua road to PON XX 2020 was generally in good condition.